The receptivity of younger generation Romanian employees to new technology implementation and its impact on the balance between work and life - Trifan, Vanina Adoriana; Pantea, Mioara Florina (Journal of Business Economics and Management, 2023)
In the current era, technological advancement has completely changed many facets of our daily lives, such as the workplace, where modern-day companies are compelled to take proactive actions. Employees face the same challenges by shifting their practices from conventional to more innovative ones. This study explores Generation Z and Millennials‘ receptivity to technological advancement and how it impacts their personal and professional lives. By exploring four personalitybased characteristics – optimism, innovation, discomfort, and insecurity – this study develops clear pathways from the perspective of Romanian younger employees. The proposed research hypotheses were tested with a sample of 399 employees, and quantitative data analysis was carried out using partial least squares structural equation modelling. Our findings are expected to provide employers, human resource managers, recruiters, and policymakers with new insights that enable them to develop methods, strategies, policies, and measures tailored to the mentality and behavioural patterns of these specific target groups.